Pendidikan Ekologi Perspektif Islam - Nurochman As-Sayyidi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
The writing is motivated by the ecological crisis that has impacted thoroughly and has threatened ecosystems joints. This issue is not only the responsibility of the state, but education also has a responsibility and a role to encourage and educate people to preserve and maintain the natural balance. Islam as a mainsource of Islamic education has a set of norms on how should a person as a caliph and nature as a relation, not fully explored yet in the context of giving a complete assessment of ecologicalproblems integrally. Ecological education in the perspective of Islam, has a secular and hereater orientation integrally and also have a strategic function in taking the role as the most effective institution to influence and educate generations to have an awareness and responsibility towards nature with an understanding of Islamic educational values. Results of this research is, Islam is a religion that contains basic values such as theocentric, anthropocentric and multi -dimensional as well ecocentric jurisprudence (sharia), the dimensions of theology (aqidah), dimensional character (muamalah), and the dimensions of Sufism (fundamentalvaluesbathiniyah). Qur'an and Sunnah as the true Islamic references are intended as a guide for mankind, what it implies it should not just stop at the theocentric dimension, but it contains insightson how to process the abundant natural resources. It means, Islam asa religion not only known as a religion to guide the people to practice a collection of ritual - vertical. In order to realize these objectives, ecological education in Islamic perspective ideally be able to change the paradigm of society from exploitation of the natural mindset towards explorative mindset.